2017
DOI: 10.3389/fneur.2017.00458
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms That Contribute to Bone Marrow Pain

Abstract: Pain associated a bony pathology puts a significant burden on individuals, society, and the health-care systems worldwide. Pathology that involves the bone marrow activates sensory nerve terminal endings of peripheral bone marrow nociceptors, and is the likely trigger for pain. This review presents our current understanding of how bone marrow nociceptors are influenced by noxious stimuli presented in pathology associated with bone marrow. A number of ion channels and receptors are emerging as important modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 138 publications
(127 reference statements)
2
23
0
Order By: Relevance
“…One advantage of studying the mouse knee is that it is small enough to be sectioned intact, thereby giving an overview of the entire knee. In 10-week old mice, we found that Na V 1.8 neurons densely innervated bone marrow cavities, which confirms reports in the literature that bone marrow is densely innervated by both Adand C-fiber sensory neurons 30 . It receives the greatest total number of sensory and sympathetic neurons when compared to mineralized bone and periosteum 31,32 .…”
Section: Discussionsupporting
confidence: 91%
“…One advantage of studying the mouse knee is that it is small enough to be sectioned intact, thereby giving an overview of the entire knee. In 10-week old mice, we found that Na V 1.8 neurons densely innervated bone marrow cavities, which confirms reports in the literature that bone marrow is densely innervated by both Adand C-fiber sensory neurons 30 . It receives the greatest total number of sensory and sympathetic neurons when compared to mineralized bone and periosteum 31,32 .…”
Section: Discussionsupporting
confidence: 91%
“…Another possibility is that peripheral sensitization contributes to movement-related pain in bone cancer. Bone cancer causes inflammation that activates peripheral bone marrow nociceptors through the release of inflammatory mediators, 34 which may cause a decreased threshold and increased responsiveness of nociceptors in bone marrow. TRPV2 is activated by local insulin-like growth factor I produced by activated osteoblasts in bone cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation eventually causes both the peripheral and central sensitization of neurons, leading to spontaneous joint pain at rest and hyperalgesia. Despite progress on the exact mechanism leading to the pain sensation [ 71 ], our detailed mechanistic understanding remains sketchy. However, it seems reasonable to assume that release of sensory neuropeptides such as substance P, calcitonin gene-related peptide (CGRP), and neurokinin A, contributes to the pain sensation in OA [ 62 , 72 ].…”
Section: Novel Indicationsmentioning
confidence: 99%